Succession of States in Respect of Treaties - Jana Maftei (EIRP Proceedings, 2014)
Although the issue of regulating the succession of states was forcefully expressed especially after the Second World War, in terms of emergence of new states after the decolonization process, this institution has not lost its actuality, not even in the early 21st century. The transformations, which occur within the international society and affecting the sovereignty, generate legal consequences, regarding the succession of the successor state to the treaties of the predecessor state. We have analyzed in this paper the issue of succession of states to the international treaties related to the Vienna Convention on the Law of Treaties from 1969 and The Vienna Convention on Succession of States in respect of Treaties from 1978. To the traditional framework of solving situations of state succession to treaties we have added recent and concrete dimensions that states have chosen to use in this matter. For the elaboration of the paper we have used as research methods, the analysis on issues related to the mentioned problems referring to the doctrinal views expressed in treaties and scientific papers, documentary research, interpretation of legal norms in the matter.